Public benefit and risk perceptions of nanotechnology development: Psychological and sociological aspects. (August 2020) - Kamarulzaman, Nur Aizat; Lee, Khai Ern; Siow, Kim Shyong; Mokhtar, Mazlin
Abstract: Nanotechnology enables the development of new and improved products. However, the public is also concerned about uncertain risks associated with nanotechnology-enabled products. To address this concern, the study aims to expand the understanding about public benefit and risk perceptions as a basis for the effective formulation of policy that addresses public interests. The study investigates public benefit and risk perceptions of nanotechnology development from the psychological and sociological aspects through a questionnaire survey conducted on Klang Valley, Malaysia. Analysis of variance (ANOVA) illustrates that demographics indeed influences public benefit and risk perceptions of nanotechnology development. However, public knowledge about nanotechnology exerts no effect on public benefit and risk perceptions of nanotechnology development based on independent t-tests. Simple linear regression reveals that the lack of public trust in government increases risk perception. Public attitude perceives nanotechnology to be more beneficial than risky, thus influencing benefit perception rather than risk perception. Public lifestyle, such as culture, religious beliefs and social group influence benefit perception but not risk perception. Result is expected to deliver better communication of benefit and risk of nanotechnology to the public as well as ensure an ethical policy regarding nanotechnology development. Highlights: The public is concerned about uncertain risks associated with nanotechnology-products. Understanding public perceptions of nanotechnology development is instrumental for effective policy formation. Knowledge has no effect on public perceptions towards nanotechnology development. Public perceives nanotechnology as more beneficial than risky thus increasing benefit perception. Public culture, religious beliefs and social groups influence benefit perception but not risk perception.